Nanoparticles (NPs)-mediated lncMALAT1 silencing to reverse cisplatin resistance for effective hepatocellular carcinoma therapy - Wang, Ting; Li, Qianyao; Xu, Rui; Zhao, Zixuan; Sun, Qi; Xu, Xiaoding; Li, Rong (Frontiers in Pharmacology, 2024)
Platinum-based chemotherapy has been widely used for clinical cancer treatment, but drug resistance is the main barrier to induce the poor prognosis of cancer patients. Long non-coding RNAs (lncRNAs) have been recognized as a type of new cancer therapeutic targets due to their important role in regulating cancer progression such as drug resistance. However, it is still challenged to effectively intervene the expression of lncRNAs as they are usually located at various subcellular organelles (e.g., nucleus, mitochondrion, and endoplasmic reticulum). We herein developed an endosomal pH-responsive nanoparticle (NP) platform for small interfering RNA (siRNA) and cisplatin prodrug co-delivery and effective cisplatin-resistant hepatocellular carcinoma (HCC) therapy. This co-delivery nanoplatform is comprised of a hydrophilic polyethylene glycol (PEG) shell and a hydrophobic poly(2-(diisopropylamino)ethyl methacrylate) (PDPA) core, in which cisplatin prodrug and electrostatic complexes of nucleus-targeting amphiphilic peptide (NTPA) and siRNA are encapsulated. After intravenous injection and then uptake by tumor cells, the endosomal pH could trigger the dissociation of nanoplatform and enhance the endosomal escape of loaded cisplatin prodrug and NTPA/siRNA complexes via the "proton sponge" effect. Subsequently, the NTPA/siRNA complexes could specifically transport siRNA into the nucleus and efficiently reverse cisplatin resistance via silencing the expression of lncRNA metastasis-associated lung adenocarcinoma transcript 1 (lncMALAT1) mainly localized in the nucleus, ultimately significantly inhibiting the growth of cisplatin-resistant HCC tumor.